A Visualisasi Data Penjualan CV. Waskat Karya Metal Menggunakan Pendekatan Business intelligence - Muhammad Anhar Mahebu; Ridha Sefina Samosir (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
CV. WASKAT KARYA METAL is a company engaged in the procurement and installation of garage components, room dividers with sliding and folding push systems. This company manages a lot of sales data. However, the data was never processed at all. For this problem, the researcher proposes to perform data processing by presenting data in the form of data visualization. Methods of data collection using the method of observation and interviews. The data analysis tool used is Microsoft Power BI by utilizing barchart, piechart, and card charts. The data analysis method uses the Bussiness Intelligence Roadmap. The result of this research is a dashboard that contains information related to sales so that it can help the company in making future decisions.